16 Matrix metalloproteinase inhibition is a parallel pathway to protection against reperfusion injury, both independent and additive to mitochondrial permeability transition pore inhibition. Issue 24 (24th November 2011) - Bell, R M; Hendry, C; Bruce-Hickman, D; Davidson, S; Breckenridge, R; Yellon, D M
Abstract : While matrix-metalloproteinase (MMP) inhibition protects against myocardial ischaemia/reperfusion injury, the mechanisms are poorly understood. We hypothesised that this cardioprotection is independent of mitochondrial permeability transition pore (mPTP) inhibition, the end-effector of ischaemic postconditioning (iPOC). In ex vivo and in vivo mouse hearts, we investigated whether the MMP inhibitor, ilomostat (0.25 μmol/l), at reperfusion, could engender protection in the absence of cyclophillin-D (CyPD), an initiator of mPTP opening, against injurious ischaemia/reperfusion. Ilomastat attenuated infarct size in wild type (WT) animals (37±2.8 to 22±4.3%, equivalent to iPOC, 27±2.1%, p<0.05). CyPD knockout (KO) hearts had smaller infarcts compared to their WT brethren (28±4.2%) and iPOC failed to protect, indicative of a pre-protected phenotype, yet ilomastat significantly attenuated infarct size in these hearts (11±3.0%, p<0.001). Furthermore, ilomastat was additive to the protection seen following iPOC in WT, restoring protection even after prolonged 50 min ischaemia (49±7.8 to 31±2.8%, p<0.05). Moreover, ilomastat, unlike cyclosporine, had no impact upon mPTP opening, indicating no interaction with CyPD/mPTP in isolated cardiomyocytes. We demonstrate that cardioprotection with MMP inhibition is independent of CyPD/mPTP function and can augment the protection seen following iPOC even after prolonged cardiac ischaemia, an observation that may have clinical applicability in attenuating injury in acute coronary syndromes.